High-Throughput Identification of Antihypertensive Peptides (AHTPs) and Characterization of AHTP-Derived Genes in the Lined Seahorse (Hippocampus erectus) - Huang, Yu; Chen, Xiyang; Shu, Haoyue; Xiao, Panpan; Lin, Xueqiang; Xu, Junmin; Bian, Chao; You, Xinxin; Yang, Jian; Shi, Qiong (Frontiers in Marine Science, 2022)
Recently, the prevalence of hypertension has become a global challenge. Therefore, tremendous efforts have been made to identify and purify antihypertensive peptides (AHTPs) from food-derived proteins to aid the discovery of new hypotensive drugs with fewer side effects. In this study, we performed high-throughput prediction of AHTPs based on multi-omics data, providing an overview of AHTPs in the lined seahorse proteins and suggesting their potential application as bioactive agents to lower blood pressure. We identified 14,695 AHTP-derived genes in the lined seahorse, and most of them were supported by transcriptomic evidence, whereas only 495 genes were further detected by proteome sequencing. Among these predicted AHTP-derived genes, the longest titin had the most hits with 104 AHTPs, some of which were clustered in exon 158, 194, and 204. Another AHTP-rich group was in the collagen family, and four AHTP-rich collagens exhibited much higher transcription in the pouch than in other examined tissues, including brain, testis, and embryos. Additionally, antihypertensive triplets, comprised of the permutations of Gly, Pro, and Lys, prevailed in all collagen sequences due to the representative XaaYaaGly repeat units. In summary, our present findings provide a solid basis for understanding the abundance of various AHTPs in the lined seahorse as well as shed light on the development of antihypertensive products and drugs using seahorses as an important resource.